Barriers to cervical cancer screening among women in Bangladesh: A qualitative study. - Arif, Taimia B.; Akter, Shahinur; Jahan, Israt; Razu, Shaharior Rahman (International Journal of Child & Adolescent Health, 2024)
Cervical cancer is a severe hazard to the health of women that can be remedied through early detection. Poor and underdeveloped nations account for nine out of ten cervical cancer fatalities. The objective of the investigation was to ascertain the obstacles that women residing in the Khulna district of Bangladesh encounter when undergoing cervical cancer screening. From May 2021 to August 2021, this exploratory qualitative study was conducted using twenty indepth interviews (IDI) and two focus group discussions (FGD) in accordance with purposive sampling. Data were collected from married women aged 18 years and older using checklists and interview guides. The study yielded six themes, which indicate that the participants possessed a lower level of knowledge, attitude, and belief in relation to cervical cancer screening. Also, women in rural areas were less aware of cervical issues and experienced a greater degree of suffering than their urban counterparts. Diverse socio-demographic, economic, cultural, psychological, individual, and healthcare system-related obstacles existed. The study concludes that to impede cervical cancer, it is essential to raise awareness through advocacy, telecasting this issue on social media, and including this issue in the National Curriculum and Textbook Board of Bangladesh (NCTB) books. This will ensure that not only women, but also men, are aware of the issue.